Orobanchaceae parasite–host interactions. Issue 1 (10th December 2020) - Mutuku, J. Musembi; Cui, Songkui; Yoshida, Satoko; Shirasu, Ken
Summary: Parasitic plants in the family Orobanchaceae, such as Striga, Orobanche and Phelipanche, often cause significant damage to agricultural crops. The Orobanchaceae family comprises more than 2000 species in about 100 genera, providing an excellent system for studying the molecular basis of parasitism and its evolution. Notably, the establishment of model Orobanchaceae parasites, such as Triphysaria versicolor and Phtheirospermum japonicum, that can infect the model host Arabidopsis, has greatly facilitated transgenic analyses of genes important for parasitism. In addition, recent genomic and transcriptomic analyses of several Orobanchaceae parasites have revealed fascinating molecular insights into the evolution of parasitism and strategies for adaptation in this family. This review highlights recent progress in understanding how Orobanchaceae parasites attack their hosts and how the hosts mount a defense against the threats.